A critical appraisal of foreign language research in content and language integrated learning, young language learners, and technology-enhanced language learning published in Spain (2003–2012). (18th June 2015) - Dooly, Melinda; Masats, Dolors
Abstract : This state-of-the-art review provides a critical overview of research publications in Spain in the last ten years in three areas of teaching and learning foreign languages (especially English): context and language integrated learning (CLIL), young language learners (YLL), and technology-enhanced language learning (TELL). These three domains have been selected for their relevance to current education policies and practices in Spain. This review aims to provide access for international readers to research published in Spain in the local languages or in English, within these innovative fields. El presente artículo ofrece una mirada crítica a las investigaciones en torno a la enseñanza y aprendizaje de lenguas extranjeras en España en los últimos diez años. Este estado de la cuestión presta especial atención al inglés y aborda tres ejes que tienen gran relevancia en las actuales políticas educativas y las prácticas docentes en España: la introducción temprana de una lengua extranjera, el aprendizaje integrado de contenidos y lenguas extranjeras (AICLE) y el aprendizaje de lenguas asistido por ordenador (ALAO). Este artículo pretende divulgar internacionalmente los estudios publicados en el ámbito nacional, en inglés y en las lenguas vernáculas, en estas áreas de innovación.